Manifestation of Patience as a Coping Mechanism in Islamic Psychology: A Comparative Analysis of Sociocultural Contexts of Indonesian and Egyptian Students - Syafii, Muhammad Hisyam; Azhari, Husain (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
This study analyzes the manifestation of patience as a coping mechanism in Islamic psychology, focusing on the comparison of sociocultural contexts between Indonesian and Egyptian students. The background of this study emphasizes the importance of patience as a stress management strategy in Islam, which can be affected by cultural differences. The research used a mixed-method approach, combining a quantitative survey and qualitative interviews. The survey involved 100 university students, 50 each from Indonesia and Egypt, to measure the level of patience and coping mechanisms, while in-depth interviews were conducted with 20 students to explore their sociocultural understanding. The results showed that there were no significant differences between Indonesian and Egyptian students in terms of manifestations of patience, with identical mean scores of sociocultural context and coping mechanisms in both groups (82.54 and 82.96). However, qualitative interviews revealed differences in how they interpreted patience; Indonesian students tended to see patience as a means of maintaining social harmony, while Egyptian students emphasized the spiritual aspect guided by religious teachings. The conclusion of this study is that patience as a coping mechanism in Islamic psychology has a universal foundation, but the sociocultural context affects its interpretation and application. The findings have significance for the development of culturally sensitive psychological interventions, especially in supporting Muslim students in dealing with academic stress and other life challenges.